2015
DOI: 10.1509/jmr.10.0386
|View full text |Cite
|
Sign up to set email alerts
|

Money, Time, and the Stability of Consumer Preferences

Abstract: Consumers often make product choices that involve the consideration of money and time. Building on dual-process models, the authors propose that these two basic resources activate qualitatively different modes of processing: while money is processed analytically, time is processed more affectively. Importantly, this distinction then influences the stability of consumer preferences. An initial set of three experiments demonstrates that, compared with a control condition free of the consideration of either resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 67 publications
(115 reference statements)
0
32
0
Order By: Relevance
“…Additional research could delve into this reasoning and extend the construct to capture this element. Interesting parallels might emerge with pricing literature that shows that price is both a desirable quality indicator and an undesirable indicator of expenses (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Additional research could delve into this reasoning and extend the construct to capture this element. Interesting parallels might emerge with pricing literature that shows that price is both a desirable quality indicator and an undesirable indicator of expenses (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Given that money functions as a tool for economic exchange, there exists a strong association between money and its utility (Lee, Lee, Bertini, Zauberman, & Ariely, ). Correspondingly, monetary thoughts activate a mindset of market pricing in which social relations are seen in transactional terms with inputs (costs) and expected outputs (benefits) (Fiske, ).…”
Section: Introductionmentioning
confidence: 99%
“…A dollar is much easier to cognitively process than time, they said. Lee, Lee, Bertini, Zauberman and Ariely (2015) found that money elicits rational reactions, while time generates emotions instead. They say that priming on money vs. time will elicit different behaviors downstream, including product attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%